Development of student worksheets on ecosystem interaction concepts through an integrated environmental approach to critical thinking skills - Nisvie Nur Salsabilla; M. Arsyad; Amalia Rezeki (HAFECS PRESS, 2025)
In 21st century education, cultivating critical thinking is recognized as a vital skill that students must acquire. However, according to findings from the PISA survey, Indonesian students still lag behind in this area, scoring only 55.8%, which is below the OECD average of 58.5%. This research focuses on developing student worksheets (LKPD) that incorporate an environmental perspective to enhance the critical thinking abilities of high school students, particularly within the topic of interactions among ecosystem components. The development process adopted the ADDIE framework comprising analysis, design, development, implementation, and evaluation stages. Data were gathered using interviews, student needs assessments, expert reviews of the materials and tools, as well as practicality and effectiveness evaluations through pre- and post-tests. Validation results indicated that the LKPD achieved a very high validity rating, with scores ranging between 88% and 100%. Student feedback from the practicality test was overwhelmingly positive, with an average score of 91%, indicating a high level of usability. Furthermore, the effectiveness test demonstrated a significant improvement in students' critical thinking skills, reflected in a high average N-gain score of 0.74. These findings underscore the pedagogical value of integrating environmental contexts into science instruction, offering an empirically validated framework for strengthening critical thinking and advancing 21st-century competencies in biology education. Abstrak. Pendidikan abad 21 menuntut keterampilan berpikir kritis sebagai bagian dari kompetensi utama yang harus dimiliki peserta didik. Faktanya berdasarkan hasil survei PISA, tingkat berpikir kritis siswa Indonesia masih tergolong rendah dengan nilai 55.8% dari 58.5% rata-rata OECD (Organization for Economic Cooperation and Development). Penelitian ini bermaksud guna mengembangkan lembar kerja peserta didik (LKPD) melalui pendekatan lingkungan terintegrasi keterampilan berpikir kritis siswa SMA pada subkonsep interaksi antar komponen ekosistem. Penelitian ini menerapkan metode research and development (R&D) dengan model ADDIE, melalui tahapan analyze, design, development, implement dan evaluate. Teknik pengumpulan data mencakup wawancara, angket kebutuhan siswa, validasi ahli perangkat, validasi ahli materi, uji kepraktisan siswa serta uji keefektifan melalui pretest dan posttest. Hasil validasi menemukan bahwasanya LKPD yang dikembangkan memperoleh kriteria sangat valid dengan skor rata-rata 88–100%. Uji kepraktisan juga menunjukkan respons sangat positif dari peserta didik dengan skor rata-rata 91% dengan kriteria sangat praktis. Uji keefektifan menunjukkan bahwa penggunaan LKPD mampu meningkatkan keterampilan berpikir kritis siswa secara signifikan dengan nilai rata-rata N-gain sebesar 0,74 dengan kategori tinggi. Temuan ini menyoroti nilai pedagogis integrasi konteks lingkungan ke dalam pengajaran sains, menawarkan kerangka kerja yang tervalidasi secara empiris untuk memperkuat pemikiran kritis dan mengembangkan kompetensi abad ke-21 dalam pendidikan biologi.